Manajemen Mutu Pendidikan: Tinjauan Sistematik atas Konsep, Strategi, dan Implementasi dalam Konteks Pendidikan Indonesia - Divta Dwi Aprina; Alin Nur Indahsari; Nur Khasanah; Mu’allimin Mu’allimin (Lembaga Pengembangan Kinerja Dosen, 2025)
The quality of education is a crucial issue in human resource development, because the quality of educational services has a direct impact on learning outcomes, the relevance of graduates, and the competitiveness of the nation. However, the implementation of quality management in educational institutions still faces challenges in conceptual, strategic, and practical aspects. This article aims to answer the research question: how are the basic concepts of educational quality understood and implemented in the context of educational management in Indonesia? The method used is a literature review with a qualitative approach. Data were obtained from scientific articles sourced from Google Scholar and Publish or Perish with the keyword “basic concepts of quality.” Of the 22 articles found in the 2021–2025 range, five articles were selected through a screening and validation process for further analysis. The results of the study show three main themes. First, educational quality is understood as a quality standard that encompasses effectiveness, efficiency, and student satisfaction. Second, quality improvement strategies emphasize the role of Total Quality Management (TQM) and school-based management (SBM) involving all elements of educational institutions. Third, quality implementation is realized through academic management, learning quality, and a continuous monitoring system. The conclusion shows that education quality management is an integrated process, not only focusing on results but also on continuous improvement. Further research is recommended to expand the focus on the integration of digitalization in education quality monitoring.